UJI ORGANOLEPTIK BROWNIES KUKUS DENGAN SUBTITUSI TEPUNG BEKATUL DAN PENAMBAHAN SARI BUAH MARKISA UNGU - Hadi Kusumah, Slamet (Jurnal Ilmiah Dozen Globalindo, 2021)
The quality of brownies is an important thing that must be considered so that the product can be accepted by everyone. This study aims to determine the organoleptic value of steamed brownies with bran flour substitution and addition of purple passion fruit juice with different percentages. The research method used was experimental using a completely randomized design. The factors studied were the number of substitutes for bran flour used with concentrations (25%, 35%, 45%, 55%, 65%) and purple passion fruit juice with concentrations (5%, and 10%). The treatment was carried out twice. The test conducted was an organoleptic test covering parameters of aroma, color, taste, and texture which were assessed by 25 untrained panelists. The data obtained were then analyzed using Ms. Excel and given a descriptive study. The results showed that the steamed brownie with the best aroma was sample A4B2 (55% bran flour and 10% purple passion fruit juice) with a chocolate and passion fruit aroma. The steamed brownies that had the best color were the A3B2 sample (45% bran flour and 10% purple passion fruit juice) which was dark brown and attractive. The steamed brownie that had the best taste was sample A5B2 (65% bran flour and 10% purple passion fruit juice) with a sweet taste and dominant chocolate flavor. The steamed brownies that had the best taste was sample A1B1 (25% bran flour and 10% purple passion fruit juice) with the resulting texture being soft, tight pores, and moist.